2011
DOI: 10.1002/ajmg.a.34220
|View full text |Cite
|
Sign up to set email alerts
|

Eighteen‐year follow‐up of a patient with cobalamin F disease (cblF): Report and review

Abstract: Cobalamin F disease (cblF) is a rare disorder of intracellular cobalamin metabolism resulting in failure to thrive, recurrent stomatitis, skin rash, megaloblastic anemia, hypotonia, seizures, and intellectual disability. Data on long-term outcomes are not available. We report on the outcome of a patient with cblF disease with a frameshift mutation in the LMBRD1 gene after 18 years of intramuscular hydroxycobalamin treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 14 publications
(15 reference statements)
0
7
0
Order By: Relevance
“…Three patients died at 5, 9, and 10 months, respectively (Shih et al 1989 ; Bowron et al 2005 ; Alfadhel et al 2011 ). In some early treated patients, neurocognitive outcome was good (Miousse et al 2011 ; Armour et al 2013 ), while in others severe developmental delay was present (Gailus et al 2010 ; Alfadhel et al 2011 ). For the cblJ defect (Coelho et al 2012 ), clinical information on treatment outcome is extremely limited.…”
Section: Resultsmentioning
confidence: 99%
“…Three patients died at 5, 9, and 10 months, respectively (Shih et al 1989 ; Bowron et al 2005 ; Alfadhel et al 2011 ). In some early treated patients, neurocognitive outcome was good (Miousse et al 2011 ; Armour et al 2013 ), while in others severe developmental delay was present (Gailus et al 2010 ; Alfadhel et al 2011 ). For the cblJ defect (Coelho et al 2012 ), clinical information on treatment outcome is extremely limited.…”
Section: Resultsmentioning
confidence: 99%
“…References: Fischer et al 2014; Al Essa et al 1999; Al Tawari et al 2002; Alfadhel et al 2011; Andersson et al 1999; Andersson and Shapira 1998; Arai and Osaka 2011; Arn et al 1998; Atkinson et al 2014; Augoustides-Savvopoulou et al 1999; Backe et al 2013; Baumgartner et al 1979a; Baumgartner et al 1979b; Beauchamp et al 2009; Bellini et al 1992; Ben-Shachar et al 2012; Biancheri et al 2002; Biancheri et al 2001; Biotti et al 2014; Birnbaum et al 2008; Bishop et al 2008; Brandstetter et al 1990; Broomfield et al 2014; Brunel-Guitton et al 2010; Brunelli et al 2002; Cappuccio et al 2014; Carmel et al 1980; Carmel et al 1988; Carrillo-Carrasco et al 2009; Carrillo-Carrasco et al 2012a, b; Cerone et al 2000; Chang et al 2011; Clayton et al 1986; Coelho et al 2008; Cogan et al 1980; D’Aco et al 2014; D’Alessandro et al 2010; De Bie et al 2009; Dionisi-Vici et al 2013; Ellaway et al 1998; Engelbrecht et al 1997; Enns et al 1999; Fuchs et al 2012; Geraghty et al 1992; Gerth et al 2008; Goodman et al 1970; Goyette et al 1996; Goyette et al 1995; Goyette et al 1994; Grant et al 2009; Grünert et al 2011; Guigonis et al 2005; Gulati et al 1997; Haan et al 1985; Harding et al 1997; Harpey et al 1981; Haworth et al 1993; Holme and Ronge 1989; Howard et al 1997; Huemer et al 2005, 2014, 2015a, b; Hyland et al 1988; Kanwar et al 1976; Kind et al 2002; Lesesve and Latger-Cannard 2013; Levy et al 1970; Longo et al 2005; Lossos...…”
Section: Methodsmentioning
confidence: 99%
“…These tests showed a decline in attention and executive functions, while other skills were relatively spared (Beauchamp et al 2009). Developmental delay with impairment of verbal and non-verbal cognitive skills was also documented at follow-up of cblF patients despite treatment (Alfadhel et al 2011; Gailus et al 2010), but in some early treated patients, neurocognitive outcome was satisfactory (Miousse et al 2011; Armour et al 2013). Information on outcome in the cblJ defect (Coelho et al 2012) is extremely limited; two reported patients responded well to methylcobalamin (Kim et al 2012).…”
Section: Which Parameters Allow Valid and Timely Laboratory Diagnosis?mentioning
confidence: 97%
“…Early institution of intramuscular hydroxocobalamin corrects the biochemical abnormalities of hyperhomocysteinaemia and methylmalonic acidaemia and appears to limit the severity of cognitive and neurological impairment [ Alfadhel et al, 2011 ]. Although late institution of intramuscular hydroxocobalamin corrected the biochemical profile in our patient, there has unfortunately been no effect on the severity of the patient's developmental delay, though there appears to be a trend of improvement in growth paramaters.…”
Section: Discussionmentioning
confidence: 99%
“…Cobalamin F (cblF) is a co-factor in the vitamin B 12 metabolism pathway, encoded by the LMBRD1 gene on chromosome 6q13 [ Rutsch et al, 2009 ]. Deficiency is inherited in an autosomal recessive fashion, characteristically associated with intrauterine growth restriction, failure to thrive, congenital heart disease, developmental delay, macrocytic anaemia, neutropaenia, thrombocytopaenia, hyperhomocysteinaemia and methylmalonic aciduria [ Alfadhel et al, 2011 ]. It is usually diagnosed through urine organic acid and plasma amino acid analysis.…”
Section: Novel Insightsmentioning
confidence: 99%